Defoliation Epidemic of Ascotis selenaria Imparata Walk. (Lepidoptera: Geometridae) in Sal forest of Asarori Range, West Dehra Dun Division - Singh, Pratap; Thapa, R. S. (Indian Forester, 1988)
An defoliation epidemic by Ascotis selenaria imparata (Lepidoptera : Geometridae) started in the Sal forests of Mohammadpur Block of Asarori Range, West Dehra Dun Division in early 1975. Compartments 4, 5 and 6 were affected. In compartments 4 and 5 complete defoliation of Sal trees occurred whereas in compartment 6 trees were partially defoliated. In the understorey, trees of Mallotus philippinensis and Murraya koenigii were also badly defoliated. Two generations of the defoliator were completed by June-July, 1975 and a third generation started in the month of July. However the third generation larvae got completely annihilated by the infection of a nuclear polyhedrosis virus and the epidemic came to an abrupt end. Observations on the biology and natural enemy complex of the pest and the resultant impact of defoliation epidemic on Sal trees have been made. Control measures using insecticides and pathogens have also been suggested.